Особливості екологічного бухгалтерського обліку та аудиту в Україні в сучасних умовах - Синяєва, Людмила Василівна; Синяева, Людмила Васильевна; Syniaieva, Liudmyla; Кондратюк, О. В.; Kondratiuk, O. V.; Микульський, В.С.; Mykulskyi, V. S. (Мелітополь: Вид-во Мелітопольська типографія «Люкс», 2017)
UK: Стаття присвячена виявленню особливостей екологічного бухгалтерського обліку та аудиту в сучасних умовах. Розглянуті питання уточнення і розвитку концептуальних підходів до розкриття сутності екологічного аудиту. З метою інтеграції обліково-аналітичного забезпечення в умовах екологічної кризи до ін-формаційної системи бухгалтерського екологічного обліку управління аграрними підприємствами, запропоновано доповнити систему бухгалтерського обліку відповідними рахунками та субрахунками, які б відображали даний напрямок у діяльності економічного суб’єкта. EN: The article is devoted to revealing features of ecological accounting and auditing in modern conditions. The questions of refinement and development of conceptual approaches to the disclosure of the essence of environmental audit are considered, since the level of theoretical studies of accounting and auditing in Ukraine in modern conditions is far behind the existing needs in the agrarian sector of the economy. The features of accounting require additional study, necessary argumentation qualitatively new approach to obtaining accounting information that is used to manage the efficiency of the industry. According to this, there are tasks that require the formation of accounting and analytical support for environmental management, improving the efficiency of the operation of production systems. The current state of accounting and analytical support does not meet the requirements of the market and needs to be improved through the introduction of environmental accounting. Accounting and analytical systems are an indicator that allows you to control: rationality of management; fair redistribution of natural resources; economic measurement of natural resources; production of environmentally friendly products; identification of environmental risks; investment in the agrarian sector; negative impact on the environment. In order to integrate accounting and analytical support in the conditions of the ecological crisis into the information system of the ecological accounting of agrarian enterprises management, we are proposing to supplement the accounting system with relevant accounts and subaccounts that reflect this direction in the activities of the economic entity.
Peculiarities of the environmental accounting and audit in Ukraine in modern conditions
Keywords: екологічний облік; бухгалтерський облік; аудит; екологічна звітність; інноваційні процеси; ecological accounting; audit; environmental reporting; innovation processes; accounting information